MEMBENTUK MENTAL ENTERPRENEUR ANAK DENGAN PROJECT BASED LEARNING - Farhatin Masruroh; Riskiyana Riskiyana; Heny Wulandari (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2022)
This research was carried out as an effort to foster a child's entrepreneurial spirit through the project method by using used goods to become a unique work. The purpose of this study is to describe the implementation of efforts to form entrepreneurial mentality in early childhood through the project method and to find out the results of implementing efforts to form entrepreneurial mentality in early childhood through the project method. The type of research used is classroom action research (CAR) by conducting investigations, solving problems which are carried out in cycles. Each cycle consists of planning, action, observation, and reflection with the aim of improving the quality and results of learning in the classroom. The results of the action research found are: The form of implementation forms the entrepreneurial mentality of students carrying out project activities making works from used materials, followed by buying and selling activities. The results obtained by the children through this project method in group B at RA Baiturrahman sidodadi Banyuputih Situbondo in cycle I reached 54.54% of children who were able to achieve learning mastery (KB) out of a total of 33 people, and in cycle II, children's creative abilities were already visible. in 28 children, it means that 87.87% have fulfilled learning completeness.